2017
DOI: 10.1111/jcmm.13272
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐genic pattern found in rare type of hypopituitarism: a whole‐exome sequencing study of Han Chinese with pituitary stalk interruption syndrome

Abstract: Pituitary stalk interruption syndrome (PSIS) is a rare type of hypopituitarism manifesting various degrees of pituitary hormone deficiency. Although mutations have been identified in some familial cases, the underpinning mechanisms of sporadic patients with PSIS who are in a vast majority remain elusive, necessitating a comprehensive study using systemic approaches. We postulate that other genetic mechanisms may be responsible for the sporadic PSIS. To test this hypothesis, we conducted a study in 24 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 41 publications
4
17
0
Order By: Relevance
“…In most published series [3,4,[8][9][10][11][12][13], PSIS exhibited a male predominance, similar to what is observed in our cases. e underlying reason behind this phenomenon is unknown, though there is a selection bias in such patients since boys, more than girls, are brought by parents for growth assessment.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In most published series [3,4,[8][9][10][11][12][13], PSIS exhibited a male predominance, similar to what is observed in our cases. e underlying reason behind this phenomenon is unknown, though there is a selection bias in such patients since boys, more than girls, are brought by parents for growth assessment.…”
Section: Discussionsupporting
confidence: 90%
“…Presence of many probable pathogenic genes and heritage from normal parents are implicative of polygenic etiology of sporadic cases of PSIS [10]. Similar findings were found in Guo et al's study in which a group of gene mutations was identified in 92% of the patients and genes NCOR2, ZIC2, and NKD2 were found to be mostly associated with Notch, Shh, and Wnt signaling pathways, respectively [11].…”
Section: Discussionsupporting
confidence: 79%
“…As previously proposed by Reis et al (), we hypothesize that the frequently reported phenotypic variability and incomplete penetrance of BMP4 mutations, may be explained by the aggregate interaction/contribution of additional genetic variants or predisposing factors, inherited according to an oligogenic pattern, as recently suggested for other clinical presentations of congenital hypopituitarism by three independent groups who approached the genetic analysis of a limited number of patients with specific forms of congenital hypopituitarism by whole exome sequencing (Guo et al, ; Simm et al, ; Zwaveling‐Soonawala et al, ). While only the article by Zwaveling‐Soonawala et al, (2017) reported the identification of a novel in‐frame BPM4 deletion in one of the examined patients, all three studies suggested a polygenic etiology in a significant proportion of the examined patients (83, 65, and 30%, respectively).…”
Section: Discussionmentioning
confidence: 56%
“…Similarly, Guo et al (39) performed a WES on 24 sporadic PSIS Chinese patients to search for synergistic genetic interactions. They identified 41 heterozygous variants in genes that are either members of or associated with the Notch, SHH and Wnt signaling pathways.…”
Section: Polygenic Hypothesismentioning
confidence: 99%